Optical characterization of DNA origami-shaped silver nanoparticles created through biotemplated lithography. Issue 27 (20th June 2022) - Kabusure, Kabusure M.; Piskunen, Petteri; Yang, Jiaqi; Kataja, Mikko; Chacha, Mwita; Ojasalo, Sofia; Shen, Boxuan; Hakala, Tommi K.; Linko, Veikko
Abstract : Metal nanostructures created with Biotemplated Lithography of Inorganic Nanostructures (BLIN) were characterized optically for the first time. The feasibility for fabricating Raman-active substrates and other plasmonic structures was demonstrated. Abstract : Here, we study optically resonant substrates fabricated using the previously reported BLIN (biotemplated lithography of inorganic nanostructures) technique with single triangle and bowtie DNA origami as templates. We present the first optical characterization of BLIN-fabricated origami-shaped silver nanoparticle patterns on glass surfaces, comprising optical transmission measurements and surface-enhanced Raman spectroscopy. The formed nanoparticle patterns are examined by optical transmission measurements and used for surface enhanced Raman spectroscopy (SERS) of Rhodamine 6G (R6G) dye molecules. Polarization-resolved simulations reveal that the higher SERS enhancement observed for the bowties is primarily due to spectral overlap of the optical resonances with the Raman transitions of R6G. The results manifest the applicability of the BLIN method and substantiate its potential in parallel and high-throughput substrate manufacturing with engineered optical properties. While the results demonstrate the crucial role of the formed nanogaps for SERS, the DNA origami may enable even more complex nanopatterns for various optical applications.